War Strategy of Acehnese and Dutch in the Aceh War 1873-1912 - Ratih Rachma Kurnia; Guntur Eko Saputro; Lukman Yudho Prakoso (UIN Sumatera Utara Medan, 2023)
Nanggroe Aceh Darussalam in the history of the struggle of the Indonesian nation is the most difficult area to conquer by the Dutch. This area was once a Sultanate area that was crowded with international traders because of its strategic location. The war began when the Dutch tried to control the Aceh region so it received fierce resistance from the sultanate and the people of Aceh. The war between the Acehnese and Dutch people lasted between 1873 and 1912 which was the largest war during colonialism in the archipelago. The Acehnese and Dutch people in this long war implemented strategies with the aim of weakening the opponent's defenses. This paper aims to explain the strategies of both sides in the Aceh War. The author uses qualitative methods with library study as well as documentation to collect historical information with historiographic techniques. The result of this research was that the strategy of the Acehnese people with the spirit of fisabilillah war, deceitful tactics, and guerrilla was able to make the Dutch with higher-tech troops overwhelmed to deal with it. Meanwhile, the Dutch used war diplomacy to gain support from regional leaders with the politics of fighting and analyze the socio-cultural aspects of the Acehnese people to weaken the opponent's defenses.